2009
DOI: 10.1002/elps.200900340
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic exclusion for the selective transport of small molecules

Abstract: A novel method capable of differentiating and concentrating small molecules in bulk solution termed "electrophoretic exclusion" is described and experimentally investigated. In this technique, the hydrodynamic flow of the system is countered by the electrophoretic velocity to prevent a species from entering into the channel. The separation can be controlled by changing the flow rate or applied electric field in order to exclude certain species selectively while allowing others to pass through the capillary. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 52 publications
3
31
0
Order By: Relevance
“…While this thought experiment itself is unimportant, it certainly foretells of more recent work exploiting a stagnation region near a capillary or channel entrance which exceeds diffusion/dispersion. 5,10,11,27,28 Within the chosen system, the velocities vary dramatically and are a good test of the simulation and visualization. Four points are noted on the 2D velocity map (Figure 4), where points B and D are noted to contrast the predominance of either horizontal or vertical components while A and C differ greatly in magnitude.…”
Section: Predictions From Velocity Fieldsmentioning
confidence: 99%
See 2 more Smart Citations
“…While this thought experiment itself is unimportant, it certainly foretells of more recent work exploiting a stagnation region near a capillary or channel entrance which exceeds diffusion/dispersion. 5,10,11,27,28 Within the chosen system, the velocities vary dramatically and are a good test of the simulation and visualization. Four points are noted on the 2D velocity map (Figure 4), where points B and D are noted to contrast the predominance of either horizontal or vertical components while A and C differ greatly in magnitude.…”
Section: Predictions From Velocity Fieldsmentioning
confidence: 99%
“…In the example shown ( Figure 5), the device area covered by the streamlines and the final profile during a steady flow (parabolic flow profile with higher velocities near the center) was well behaved. In the design of an electrophoresis experimental setup, and specifically for the ones where capture of some particular species is envisioned, 5,10,11,27,28 it is important to know within-the-fluid connection paths between points within the device. While spatial velocity components might exist for the complete region-of-interest (ROI) (and apparent from the velocity vector fields) this does not inherently indicate the possibility of movement (transfer) of particles from one point to another within the ROI.…”
Section: Performance Of Particle Position Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups continue to develop variations on standard electrophoretic separation techniques, including Astorga-Wells [14], Gebauer [15,16], Hayes [17,18], and Ivory [19,20], but the current article will center on elements that are essentially new or are significant advances in strategies that uniquely exploit microfluidic formats. The advantages of microfluidic devices include lower sample consumption, portability, and shorter analysis times.…”
Section: Introductionmentioning
confidence: 97%
“…future science group exclusion, was recently described by Meighan et al for selectively isolating analytes from background interferants [12]. The authors have shown that analytes can be enriched and separated under a steady hydrodynamic bulk flow (gravity, in this example) toward the detector and electrophoretic migration away from the capillary inlet.…”
mentioning
confidence: 95%